2004
DOI: 10.1128/iai.72.8.4410-4415.2004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum Cytokines in Patients with Severe Acute Respiratory Syndrome

Abstract: Severe acute respiratory syndrome (SARS) is an acute infectious disease of the respiratory system. Although a novel coronavirus has been identified as the causative agent of SARS, the pathogenic mechanisms of SARS are not understood. In this study, sera were collected from healthy donors, patients with SARS, patients with severe SARS, and patients with SARS in convalescence. The serum concentrations of interleukin-1 (IL-1), IL-4, IL-6, IL-8, IL-10, tumor growth factor beta (TGF-␤), tumor necrosis factor alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
342
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(370 citation statements)
references
References 23 publications
17
342
2
2
Order By: Relevance
“…In fact, raised levels of IL-6 and IL-8 have also been reported from SARS patients in Guangzhou [84] and Taiwan [85]. Xie et al [86] and Zhang et al [87] report raised levels of IL-8 and IL-6 respectively. Some of these studies [77,87] and others [88] have also reported raised levels of IL-10.…”
Section: Pathogenesismentioning
confidence: 84%
See 1 more Smart Citation
“…In fact, raised levels of IL-6 and IL-8 have also been reported from SARS patients in Guangzhou [84] and Taiwan [85]. Xie et al [86] and Zhang et al [87] report raised levels of IL-8 and IL-6 respectively. Some of these studies [77,87] and others [88] have also reported raised levels of IL-10.…”
Section: Pathogenesismentioning
confidence: 84%
“…Xie et al [86] and Zhang et al [87] report raised levels of IL-8 and IL-6 respectively. Some of these studies [77,87] and others [88] have also reported raised levels of IL-10.…”
Section: Pathogenesismentioning
confidence: 99%
“…Research suggests that immunopathologic damage from an overexuberant host immune response, rather than uncontrolled viral replication, was the major cause of lung damage at this stage. 48,50,69,77 …”
Section: Human Cases Of Sars Clinical Featuresmentioning
confidence: 99%
“…16,17,47,58,66,75 Investigation of the cytokine and chemokine profiles of SARS patients has suggested that severe SARS-related lung injury might be attributed to an excessive host immune response-particularly, the deregulation of proinflammatory cytokine production. 48,50,68,77 Wild Animals and Domestic Animals in the Market…”
Section: Pathologic Changesmentioning
confidence: 99%
“…Cytokines are widely recognized as important mediators of inflammatory response [13]. For instance, IL-6 is a proinflammatory cytokine that induces the terminal differentiation of proliferating B cells to plasma cells, stimulates antibody secretion, and enhances T-lymphocyte responses in secondary lymphoid organs [14].…”
Section: Introductionmentioning
confidence: 99%